“That Heavy Machine”: Reprising the Colonial Apparatus in 21st-Century Social Control - Brown, Mark (Social justice, 2005)
Part of a special issue on emerging imaginaries of regulation, control, and repression. Since the 1980s, dangerous criminals have become subject to numerous increasingly punitive sanctions and strategies of exclusion. In the area of sentencing, for example, governments have formulated a doctrine of “public protection” that is now favored over traditional juridical principles of parsimony and proportionality. This change has occurred in an environment in which traditional sources of authority on punishment and crime control have been moved to the margins in order to permit a strong current of popular sentiment to enter and shape debates on punishment policy and responses to crime.